2023
DOI: 10.1038/s41598-023-49940-2
|View full text |Cite
|
Sign up to set email alerts
|

A validated LC–MS/MS method for simultaneous determination of key glucocorticoids in animal hair for applications in conservation biology

Ilona Sadok,
Kinga Ożga,
Daniel Klich
et al.

Abstract: A new method for the determination of main glucocorticoids (cortisol, cortisone, and corticosterone) in hair by liquid chromatography-tandem mass spectrometry was developed. Glucocorticoids were extracted from hair shafts using methanol followed by solid-phase extraction. A validation test was performed using hair from three species of wild mammals with different body size (0.2–800 kg), lifestyle (terrestrial, burrowing and arboreal species), social organization (living in herds or solitary), and different pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In hair samples, cortisol and its metabolite-cortisone were determined using a validated ultra-high performance liquid chromatography coupled to electrospray ionization-tandem mass spectrometry (UHPLC-ESI-MS/ MS) method. We decided to follow the concentration of two steroids in the hair because it has beed suggested that measuring multiple glucocorticoids simultaneously may provide more comprehensive information and more reliable interpretation of the acquired results [34]. The method of sample preparation and analysis was described in detail by Sadok et al [34].…”
Section: Determination Of Hair Steroids (Cortisol and Cortisone)mentioning
confidence: 99%
See 4 more Smart Citations
“…In hair samples, cortisol and its metabolite-cortisone were determined using a validated ultra-high performance liquid chromatography coupled to electrospray ionization-tandem mass spectrometry (UHPLC-ESI-MS/ MS) method. We decided to follow the concentration of two steroids in the hair because it has beed suggested that measuring multiple glucocorticoids simultaneously may provide more comprehensive information and more reliable interpretation of the acquired results [34]. The method of sample preparation and analysis was described in detail by Sadok et al [34].…”
Section: Determination Of Hair Steroids (Cortisol and Cortisone)mentioning
confidence: 99%
“…We decided to follow the concentration of two steroids in the hair because it has beed suggested that measuring multiple glucocorticoids simultaneously may provide more comprehensive information and more reliable interpretation of the acquired results [34]. The method of sample preparation and analysis was described in detail by Sadok et al [34]. Briefly, hair samples were washed twice with isopropanol, dried overnight, cut into small pieces into a tube in an amount from 16 to 48 mg, and milled using steel beads.…”
Section: Determination Of Hair Steroids (Cortisol and Cortisone)mentioning
confidence: 99%
See 3 more Smart Citations